Animation in Motion: Political Economy Leverage of East Asia for Global Influence - Darynaufal Mulyaman; Nicholas Jevon Manuela Putra; Audrey Gracias Herlambang (East Asian Review, 2026)
This study examines how anime and East Asian animation function as instruments of cultural diplomacy and soft power within the framework of behavioral political economy. Specifically, it investigates the mechanisms through which Japan, South Korea, and China leverage animated cultural products to project influence, shape audience behavior, and generate economic returns in global markets. Employing a qualitative approach through comparative analysis and systematic literature review, this research draws on industry reports, peer-reviewed journals, and policy documents to trace anime's historical development, international market penetration, and its role within the Cool Japan Initiative and Hallyu Wave. The findings reveal that anime operates as a dynamic form of cultural behavioral multilateralism, wherein global audiences do not passively receive Japanese cultural content but actively reinterpret and localize it, generating reciprocal flows of influence. Comparatively, South Korea has repositioned itself from subcontractor to global IP producer, while China has pursued state-backed domestic consolidation as its primary model of cultural expansion. Economically, East Asian animation diversifies national revenue through streaming, merchandising, and licensing, while politically it sustains cross-cultural dialogue and soft power leverage even in diplomatically strained bilateral contexts. These findings suggest that animation in East Asia functions simultaneously as an economic motor and a geopolitical asset whose influence is co-produced between origin states and global audiences.